Bending frustration of lipid−water mesophases based on cubic minimal surfaces - Schwarz, Ulrich S.; Gompper, Gerhard (Langmuir, 2001)
Inverse bicontinuous cubic phases are ubiquitous in lipid−water mixtures and consist of a lipid bilayer forming a cubic minimal surface, thereby dividing space into two cubic networks of water channels. For small hydrocarbon chain lengths, the monolayers can be modeled as parallel surfaces to a minimal midsurface. The bending energy of the cubic phases is determined by the distribution of Gaussian curvature over the minimal midsurfaces which we calculate for seven different structures (G, D, P, I-WP, C(P), S, and F-RD). We show that the free-energy densities of the structures G, D, and P are considerably lower than those of the other investigated structures due to their narrow distribution of Gaussian curvature. The Bonnet transformation between G, D, and P implies that these phases coexist along a triple line, which also includes an excess water phase. Our model includes thermal membrane undulations. Our qualitative predictions remain unchanged when higher order terms in the curvature energy are included. Calculated phase diagrams agree well with the experimental results for 2:1 lauric acid/dilauroyl phosphatidylcholine and water.